Anti-hypercholesterolemia effects and quality of eel (Anguilla bicolor) oil - Heru Sasongko; Sugiyarto Sugiyarto; Agung Budiharjo; Nur Rohman Efendi (Universitas Sebelas Maret, 2017)
Eel (Anguilla bicolor) is a general fish consumption in many countries. Besides its vitamin rich, eel oil is also known to contain fatty acids like oleic acid and palmitic acid. That is necessary for traditional medicine and as food a supplement. It is known that polyunsaturated fatty acids are recognized to lower blood cholesterol. In this study, fresh eels were extracted using reflux methods. The study was conducted on rat test animals given high-fat diet and PTU (Propylthiouracil). Treatment was given eel fish oil with dose 0.5 ml / kg BW; 1 ml / KgBW and 2 ml / KgBW. The results of eel extraction showed that the metal content is undetectable except Zn metal 11.72 ppm. Eel fish oil affects the total cholesterol decrease at each dose (h <0.05). Known percent increase in total cholesterol after 14 days at a dose of 0.5 ml / kg body weight (-14.10%); 1 ml / kg BW (2.12%) and 2 ml / kg BW (11.37%).